FAKTOR YANG MEMPENGARUHI MOTIVASI PERAWAT MELANJUTKAN PENDIDIKAN PROFESI NERS - Eka Yuliani (Universitas Mitra Indonesia, 2021)
Factors affecting nurse motivation to continuing Ners education. One of the problems facing nurses is professionalism. The phenomenon in the hospital most of the Indonesian nurses are still educated diploma III. The purpose of this study is to analyze the factors that influence the motivation to continue nursing professional education (ners). The research design using descriptive research method with Cross Sectional approach. Number of samples of 309 nurses from three regional general hospitals in Lampung province. Data collection using proportional sampling method, that goes through the selection of samples in each room according to the inclusion criteria of nurses on the basis of education diploma III. Analysis using Chi Square and Logistic Regression. There was a significant correlation between age (p = 0.004; α <0.05) and remuneration satisfaction (p = 0.001; α <0.05) with nurse motivation to continue education. Remuneration satisfaction is the most dominant factor but it only affects the motivation of continuing education on nurse by 54%, the rest is influenced by other factors. The study recommends hospital management to improve policy concerning nurse mapping that continuing education and improvement of remuneration system of nurse as well as effort to motivate nurses in improving the quality of nursing resources.